The critical reflection profile: Working to raise the quality of teacher education in Malaysia - Somekh, Bridget; Hoon, Chang Lee; Ahmad, Noor Aini (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The focus of this article is the Critical Reflection Profile (CRP) and Guidelines which have recently been developed at Universiti Pendidikan Sultan Idris, Malaysia (UPSI). The revised Malaysian national curriculum has a new focus on critical and creative thinking. There is an opportunity to introduce critical reflection - and teacher action research - into the day-to-day practice of teachers and school leaders in Malaysia. This coincides with changes in legislation that have somewhat destabilized the school system, for example ending the teaching of mathematics and science through the medium of English. At this time of rapid change, UPSI, as one of the major providers of teacher education in Malaysia, has an important role to play in improving the quality of teacher education with consequent improvements in the quality of teaching and learning in schools. Over the last decade, UPSI has built up a vibrant tradition of action research in partnership with local schools in the State of Perak and Selangor. The current initiative builds upon this work. With the support of the vice chancellor, a group of professors and senior lecturers are working to embed critical reflection in all aspects of teacher education: pre-service and in-service courses for teachers and continuous professional development of lecturing faculty. In a country with considerable ethnic variety such as Malays, Indian, Chinese, Iban, dan Kadazan communities, it is true that the introduction of critical reflection which is grounded in educational values, requires inter-cultural sensitivity and open dialogue. The CRP has been developed as a mediating tool for this process of cultural change. The article presents the theoretical framework for critical reflection in eight dimensions upon which the new Guideline for Critical Reflection in Teaching and Learning were grounded; and explains the process envisaged for use of the CRP and its function in mediating critical reflection in teacher education.